From VA Larynx to the future of chemoselection: Defining the role of induction chemotherapy in larynx cancer. (November 2018) - Spector, Matthew E.; Rosko, Andrew J.; Swiecicki, Paul L.; Chad Brenner, J.; Birkeland, Andrew C.
Highlights: Induction chemotherapy can select patients who will respond to organ preservation therapy. The identification of biomarkers that can better predict response to organ preservation therapy. Novel induction agents, with or without cytotoxic chemotherapy, may improve response rates and be effective to expand organ preservation approaches in advanced laryngeal cancer. Abstract: Organ preservation protocols utilizing induction chemotherapy as a selection agent have played a critical role in the treatment of advanced laryngeal squamous cell carcinoma (LSCC). The selection of patients who will have a good response to chemoradiation allows for organ preservation in a significant group of patients and minimizes the rate of surgical salvage. While there remains debate regarding its utility when compared to surgery or other organ preservation regimens, the data does suggest an important role for induction chemotherapy in LSCC. In addition, there are continued opportunities to identify pretreatment biomarkers for induction chemotherapy, whether genetic, epigenetic or cellular, that could predict response to treatment and select patients to therapy (whether organ preservation or surgery). As our understanding of the biology of larynx cancer advances, induction paradigms have utility for the development and adoption of novel agents and therapeutics. The background of induction chemotherapy as a selection agent and future directions of this approach are discussed.